Pengaruh Psikologi Positif dan Kepemimpinan Terhadap Motivasi Kerja Karyawan - Feti Fatonah; Achmad Naufal; Eldo Tri Rahmadani; Faris Muhammad Fahrezi; Muhamad Adimukti Prasojo (Jurnal Manajemen, Akuntansi dan Logistik (JUMATI), 2024)
Purpose – The aim of this research is to determine (1) the influence of positive psychology on employee work motivation; (2) the influence of leadership on employee work motivation. In this study, a literature review method is employed for research. Design/methodology/approach – In this research, the systematic literature review (SLR) method is employed, which is utilized to search for national and international literature data with reputable sources in SINTA and SCOPUS. Findings – The results of this compilation and analysis are used to draw conclusions regarding the influence of psychology and leadership on employee work motivation. Research limitations/implications – The conclusions drawn from this research indicate that based on the above analysis: (1) Positive psychology encourages employees to achieve targets, overcome challenges, and adapt to changing work environment situations. (2) To enhance employee performance, companies are expected to identify and develop employees' psychological capital through the provision and improvement of various resources that support the achievement of employee goals, such as competence, autonomy, feedback, mental resilience, social support, and guidance from superiors. (3) Leadership style is one of the factors that can influence motivation. (4) Leadership style is an approach used by a leader to influence the performance of subordinates. Practical implications – The conclusion of implementing a leadership style is to provide inspiration, enthusiasm, and motivation to employees in carrying out tasks assigned by the organization.